ANALYSIS OF THE INFLUENCE OF CT, RT, WCT AND DR ON PROFITABILITY IN BASIC AND CHEMICAL INDUSTRY COMPANIES - Nina Purnasari; Eulan Dame Septiani Br Pangaribuan; Suriyani -; Rini Herliani (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Basic industry and chemical companies are one of the sectors that are in the branch of the manufacturing industry (non-oil and gas). This company plays an important role in driving the Indonesian economy. Based on data obtained from www.idx.co.id it can be seen that PT Arwana Citramulia Tbk (ARNA), which is a company engaged in the glass and porcelain industry, earned Rp. 2.15 trillion in revenue in 2019. This amount increased by 9.15% from 2018 which amounted to IDR 1.97 trillion. ARNA also recorded an increase in net profit of up to 37.61% yoy, from IDR 156.62 billion in 2018 to IDR 215.53 billion in 2019. On a yearly basis, ARNA's shares have corrected 19.72% to IDR 350 per share. Based on the test results Partially, cash turnover has no effect on profitability in companies in the Basic Industry and Chemical sectors for the 2018-2021 period listed on the IDX. 5. Based on the results of simultaneous testing of cash turnover, accounts receivable turnover, working capital turnover and debt ratios have an influence on profitability in companies in the Basic Industry and Chemical sectors for the 2018-2021 period listed on the IDX